Drag force through gases and plasma - M Apostol (Annals of Mathematics and Physics - Peertechz Publications, 2022)
The drag force in a gas (previously derived by Stokes and Rayleigh) is derived by means of the molecular kinetics (transport equation of the momentum). Two regimes of resistance to motion are identified, governed by the relation of the velocity to the thermal (molecular) velocity. They correspond to the molecular movement, for small velocities, or to the hydrodynamic motion for high velocities. In the former case sound waves are not excited, and energy is dissipated by viscosity (friction), while in the latter case the energy is dissipated by the excitation of the sound waves. Also, the treatment is applied to the plasma. It is shown that in usual plasmas it is unlikely that the body motion excites plasmons.